2007
DOI: 10.1111/j.1365-2265.2007.02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impairment in patients treated for pituitary disease: a controlled study

Abstract: At follow-up after appropriate treatment, we documented a high prevalence of psychopathology in patients with pituitary disease, which was however, similar to that found in nonpituitary endocrine patients. This is consistent with an increasing body of literature that reports difficulties in obtaining full recovery in patients treated for endocrine disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 52 publications
(114 reference statements)
1
64
1
1
Order By: Relevance
“…The emotional and psychological effects of such lingering changes have so far not been thoroughly studied. Previous studies have reported an increased risk of psychopathology and maladaptive personality traits in patients with active acromegaly and those who have been in long-term remission (8,21,22). However, to date there has been no satisfactory explanation of this phenomenon except that it may be related to irreversible changes associated with previous GH excess (8).…”
Section: Discussionmentioning
confidence: 78%
“…The emotional and psychological effects of such lingering changes have so far not been thoroughly studied. Previous studies have reported an increased risk of psychopathology and maladaptive personality traits in patients with active acromegaly and those who have been in long-term remission (8,21,22). However, to date there has been no satisfactory explanation of this phenomenon except that it may be related to irreversible changes associated with previous GH excess (8).…”
Section: Discussionmentioning
confidence: 78%
“…Glucocorticoid dose has to be tapered after successful surgery, but this is challenging for some patients who just cannot tolerate dose reduction, even several weeks or months after the surgery. Even in the long-term management of CS, being aware of these changing situations does help patients conform, with the hope of final improvement (5). Common complaints like cognitive impairments and psychiatric disorders, as well as periodic follow-ups to evaluate pituitary function and detect possible recurrences of hypercortisolism, put extra stress on these CS patients, which in turn worsens psychological issues and often leads to a bad QoL.…”
Section: Cushing's Diseasementioning
confidence: 99%
“…The application of the DCPR operational criteria has permitted to document the occurrence of demoralization across different medical settings, substantiating previous findings that used dimensional tools 20, 21 . In studies utilizing the DCPR, demoralization was found in 14-44% of patients with cardiac 22 , oncological 23 , dermatological 24 , gastrointestinal 25 and endocrine conditions [26][27][28] , in those recruited in primary care 29 and in consultation-liaison psychiatry settings 30,31 . Table 1 DCPR criteria for demoralization A through C are required A.…”
Section: Introductionmentioning
confidence: 99%